Sovereign Wealth Funds in the UAE, Egypt, and Kuwait - Al Awadhi, Talal (American Journal of Trade and Policy, 2024)
The UAE, Egypt, and Kuwait sponsor SWFs. Decision-making in the SWFs of these countries is made by the Board of Directors and management or operating committees or teams. While internal politics and geopolitics inevitably influence SWFs, the government’s direct participation in decision-making could cause concern for host countries. SWFs in the three countries are regulated under domestic law through their legal mandate and supervision by the designated government authority. The Santiago Principles and IFSWF comprise the international regulatory framework for SWFs. However, compliance is voluntary and there are no sanctions for erring members. Compliance is limited in the three countries, especially in the area of disclosure because of the close involvement in the SWFs by the ruling family in the UAE and Kuwait and the Prime Minister in Egypt. SWFs in the three countries are growing and assuming more important roles. With their expanding roles, they have to increasingly address domestic and international expectations to function more effectively. A starting point is better compliance with the Santiago Principles, which is a matter of interest in the global market. Creating a regional chapter of IFSWF can facilitate context-specific standards and compliance. Regulatory reforms can also improve the domestic investment climate to make SWFs more effective at fulfilling their purpose.
Keywords: UAE; Egypt; Kuwait; International Funds; Soverign Wealth; Funds